Effect of Serratia sp. K3 combined with organic materials on cadmium migration in soil-vetiveria zizanioides L. system and bacterial community in contaminated soil. (March 2020) - Liu, Huakang; Xie, Yanluo; Li, Junjie; Zeng, Guoquan; Li, Hao; Xu, Fei; Feng, Su; Xu, Heng
Abstract: Phytoremediation is an economical strategy to harvest cadmium (Cd) from contaminated soil, but the efficiency of phytoremediation was affected by many factors. This study investigated the potential of Serratia sp. K3 (K3) assisted with straw biogas residue (SBR) or leavening fertilizer (LF) on improving the Cd migration efficiency and micro-environment in soil- vetiveria zizanioides L. system. The results showed that the acid soluble Cd in soil was increased by 2.83–29.79% in treatments compared with control (CK). In addition, Cd accumulation in the roots and shoots of vetiveria zizanioides were significantly enhanced by the combination of K3 and SBR/LF. Especially, the translocation factor of Cd increased by 21.53–62.37% in groups with K3 compared with the groups without K3, correspondingly. Furthermore, SBR/LF effectively changed bacterial community structure, and improved bacterial abundance. Relative abundance of functional genes related with carbohydrate/energy/amino acid metabolism were increased in groups of SBRB/LFB rhizosphere compared with CK. These results provide insight into the change of phytoremediation efficiency and soil bacterial communities in the vetiveria zizanioides rhizosphere after inoculation. This study may provide a promising method for improving phytoremediation in Cd contaminated soil. Graphical abstract: Image 1 Highlights: 1 . Serratia sp. K3 with OMs enhanced cadmium bioavailability. K3 and OMs significantly improved rhizospheric soil micro-ecology. OMs were better than K3 on changing bacterial community. Synergistic effect of K3 and OMs obviously enhanced Cd translocation factor.